Papillary cystadenocarcinoma of the parotid gland: a rare sub-variant of salivary gland adenocarcinoma - Dutta, Satya; Dey, Biswajit; Mishra, Jaya; Raphael, Vandana; Das, Jonali; Lynser, Donboklang (Autopsy and Case Reports, 2022)
Papillary cystadenocarcinoma of the salivary gland is a very rare malignant neoplasm accounting for only 2% of all salivary gland lesions. In 1991 it was first included as a separate entity in the World Health Organization (WHO) classification of salivary gland tumors and in 2017 WHO Classification, the tumor was clubbed as a sub-variant of adenocarcinoma, not otherwise specified. It most commonly occurs in the major salivary glands. Herein we report a case of salivary papillary cystadenocarcinoma in a 54-year-old female, who presented with rapid enlargement of the right parotid swelling. Based on radiology and fine-needle aspiration cytology, a working diagnosis of the malignant tumor involving the superficial lobe of the right parotid gland was made. In view of the malignant nature of the swelling, superficial parotidectomy was done. The histopathology and immunohistochemistry of the mass confirmed the diagnosis of papillary cystadenocarcinoma of the right parotid. With the revised 2017 WHO classification of salivary gland tumors, it is important to report all rare subtypes in order to understand their biology and behavior.